IMMUNOTHERAPY IN PATIENTS WITH THE FIRST TYPE OF HYPERSENSITIVITY TO HYMENOPTERA VENOME - Jovanović, Dragana; Perić Popadić, Aleksandra (Medicinski podmladak, 2022)
Hymenoptera venom allergy (HVA) is an anaphylactic reaction that occurs after the sting of Hymenopteran insects: honeybee (Apis mellifera), wasp (Vespula vulgaris) or hornet (Vespa crabo). Hymenoptera insects can cause IgE-mediated hypersensitivity reactions in insect-sensitized patients, ranging from local to severe systemic reactions and even fatal anaphylaxis. Systemic allergic reactions (SAR) after Hymenoptera insect stings have been reported in up to 7.5% of adults and up to 3.4% of children. They can be limited to the skin or cause severe reactions such as dizziness, dyspnea, nausea, and loss of consciousness, shock, cardiac or respiratory arrest. Patients with HVA are advised to carry an emergency kit consisting of an epinephrine auto-injector (AAI), H1-antihistamines and corticosteroids depending on the severity of the previous SAR. The only treatment that can potentially prevent SAR is immunotherapy with the appropriate venom (VIT). VIT has been reported to be effective in 77%-84% of patients treated with bee venom and in 91%-96% of patients treated with wasp venom. The latest European Academy of Allergy and Clinical Immunology (EAACI) guidelines provide evidence-based recommendations for the use of VIT. VIT is recommended in children and adults who are hypersensitive to the venom because it leads to a significant improvement in quality of life compared to wearing an adrenaline auto-injector. By receiving increasing doses of venom over 3 to 5 years, VIT leads to a change in the immune response and tolerance to the respective venom. Molecular diagnostics, which uses recombinant allergens, enables detection of true sensitization and thus improves the selection of appropriate venom for long-term VIT. This review aims to provide information on immunotherapy recommendations, as well as risk factors for SAR during and after VIT.
Keywords: immunotherapy, Hymenoptera venoms, type I hypersensitivity